1995
DOI: 10.1002/jcp.1041650323
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase activity is associated with proliferation but not with T3‐induced differentiation of Caco‐2 cells

Abstract: Ornithine decarboxylase (ODC) activity and polyamine (putrescine, spermidine, spermine) concentrations were measured in parallel in enterocyte-like Caco-2 cells maintained under various culture conditions. ODC activity was maximal at the beginning of the exponential growth phase, decreasing dramatically thereafter to a negligible level at confluency (day 9). Kinetic studies performed on day 3 revealed the presence of a single enzyme with a Km around 200 microM and a Vmax of about 2 nmol CO2 released/h/mg prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Addition of putrescine or spermidine in the culture medium in addition to ODC inhibitor reverses almost totally the anti-proliferative effect of ODC inhibition (60)(61)(62)(63) indicating that exogenous putrescine and/or spermidine through entry into adenocarcinoma cells can substitute for endogenous production. Endogenous production of polyamines in Caco-2 cells appears to be more closely associated with cell proliferation than with cell differentiation (64). Using isolated nuclei from the human colon carcinoma cell line COLO 320, it has been shown that spermidine can increase the transcription of growth-associated genes (65).…”
Section: Synthesis Of Polyamines and Cancerous Colonic Epithelial Celmentioning
confidence: 99%
“…Addition of putrescine or spermidine in the culture medium in addition to ODC inhibitor reverses almost totally the anti-proliferative effect of ODC inhibition (60)(61)(62)(63) indicating that exogenous putrescine and/or spermidine through entry into adenocarcinoma cells can substitute for endogenous production. Endogenous production of polyamines in Caco-2 cells appears to be more closely associated with cell proliferation than with cell differentiation (64). Using isolated nuclei from the human colon carcinoma cell line COLO 320, it has been shown that spermidine can increase the transcription of growth-associated genes (65).…”
Section: Synthesis Of Polyamines and Cancerous Colonic Epithelial Celmentioning
confidence: 99%
“…ODC activity in Caco-2 cells [14,15], in human colon adenocarcinoma [16] and in ascites hepatoma cells [17] was previously reported to be maximal at the beginning of the exponential growth phase, decreasing dramatically thereafter to a negligible level at conXuency.…”
mentioning
confidence: 99%
“…The cell lines used in this study have similar characteristics to some cells of the crypt-villus axis. Caco2 cells were previously described to possess characteristics of normal small intestinal epithelium (Jumarie and Malo 1995), HT-29 and DLD1 cells are known to possess the characteristics of surface villus cells (Panja et al 1998).…”
Section: Discussionmentioning
confidence: 99%